Experimental modeling of hypothyroidism: principles, methods, several advanced research directions in cardiology - Aleksey M. Chaulin; Julia V. Grigorieva; Galina N. Suvorova; Dmitry V. Duplyakov (Russian Open Medical Journal)
Hypothyroidism is one of the most common pathological conditions in modern clinical practice. Due to the fact that the targets of thyroid hormones are virtually all organs and tissues, the morphological and clinical manifestations arising with a deficiency of thyroid hormones are quite diverse. Experimental models of hypothyroidism in laboratory animals are widely used for preclinical study of the fundamental pathophysiological mechanisms underlying hypothyroidism, as well as for assessing the effectiveness of treatment-and-prophylactic effects. Currently, several groups of effective models of hypothyroidism have been developed: dietary, surgical, medicamentous, genetic, radioactive and immunological. Each of the specified models is based on different principles, has advantages and disadvantages, and can be used depending on the goals and objectives of the experiment. In this review, we will consistently consider hypothyroidism modeling methods and indicate some promising areas of their use in cardiology.